2019
DOI: 10.2169/internalmedicine.2872-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Hospitalist System in Japan on the Quality of Care and Healthcare Economics

Abstract: Objective The hospitalist system is considered successful with respect to the quality of care and cost effectiveness in the United States. Studies have consistently demonstrated an improved clinical efficiency with this system. In Japan, however, the efficacy of the hospitalist system has not yet been examined. As a “super-aged society”, Japan has a high number of elderly patients with multiple comorbidities who may theoretically receive better care by the hospitalist system than by the conventional system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…Unlike hospitalists in the United States, 2 hospitalists in Japan provide inpatient and outpatient care. They mainly practice internal medicine and contribute to medical safety management, postgraduate clinical education, quality of medical care in the hospital, and acute care with a focus on disease management 3 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike hospitalists in the United States, 2 hospitalists in Japan provide inpatient and outpatient care. They mainly practice internal medicine and contribute to medical safety management, postgraduate clinical education, quality of medical care in the hospital, and acute care with a focus on disease management 3 …”
Section: Figurementioning
confidence: 99%
“…They mainly practice internal medicine and contribute to medical safety management, postgraduate clinical education, quality of medical care in the hospital, and acute care with a focus on disease management. 3 …”
mentioning
confidence: 99%
“…A Japanese study of elderly patients with chronic aspiration pneumonia found that care by Adoption of Hospitalist Care in Asia | Yan et al hospitalists resulted in shorter LOS and lower costs than specialist care. 19 Recently, hospitalists have played a central role in COVID-19 management, opening fever intake clinics and establishing collaborative guidelines with infectious disease experts and other specialists.…”
Section: Adoption Of Hospitalist Care Outcomes and Challenges Facedmentioning
confidence: 99%
“…According to the World Health Organization and the United Nations, a society with >21% of the population aged 65 years is defined as a “super‐aged society”. Since 2013, Japan has been classified as a “super‐aged society” 2,3 . Frailty syndrome is characterized by an increased vulnerability arising from aging‐related degeneration in psychological, physical and social functioning 4,5 .…”
Section: Introductionmentioning
confidence: 99%